Application of a mid-/low-temperature solar thermochemical technology in the distributed energy system with cooling, heating and power production. (1st November 2019) - Bai, Zhang; Liu, Qibin; Gong, Liang; Lei, Jing
Highlights: A new solar thermochemical-based cooling, heating and power system is proposed. The off-design evaluation mathematical model is developed. Varying solar irradiations and energy loads are comprehensively considered. The annual transient operation characteristics of the system are investigated. Favorable thermodynamic and economic performances can be achieved. Abstract: A new solar-assisted cooling, heating and power (CCHP) system is developed for improving the energy conversion efficiency in this work. Solar thermal energy (250–350 °C) collected by a parabolic trough solar collector is used to drive the thermochemical reaction of methanol decomposition, then the generated solar fuel in the form of syngas is fed into an internal combustion engine (ICE) to generate electricity. The high-temperature exhaust gas released by the ICE is used to produce cooling and heating energies via a double-effect LiBr-H2 O absorption refrigerator and a heat exchanger. Solar energy is converted to chemical energy in the form of syngas, the distinct advantages of energy cascade utilization and thermochemical storage can be realized. Numerical simulation results show that in the proposed CCHP system the energy and exergy efficiencies at the designate condition are 82.0% and 58.72%, respectively. The off-design performances are investigated by deploying the proposed CCHP system to a shopping center building, the annual efficiency and the solar fraction reach 53.6% and 9.81%, respectively. In comparison with the reference solar-assisted CCHP system, the annual methanol consumption of the proposed CCHP system decreases to 874.31 tons with the fuel saving ratio of 4.56% and less CO2 emission. This novel solar CCHP system presents a promising cost-effective performance and the system life cycle cost saving ratio reaches 2.84%. The research findings provide an alternative route towards efficiently utilizing solar energy.